Gagasan Islamisasi Ilmu Pengetahuan: Syed Muhammad Naquib Al-Attas Dan Intelektual Muslim Indonesia - Muhibuddin, Muhibuddin (At-Tafkir, 2022)
The Islamization of the science movement arose due to Muslim intellectual concerns about the scientific crisis experienced by Muslims because it was contaminated with secular-based Western science and was incompatible with Muslims because it separated religion from science. The purpose of this study is to raise the idea of Islamization of science by Syed Muhammad Naquib al-Attas and the response of several Indonesian Muslim intellectuals to the idea of science. By looking at the characters' essays and descriptive-analytical-critical methods, the researchers found that al-Attas offered the concept of Islamization of science and the concept of Islamic education. Meanwhile, Indonesian Muslim intellectuals offer the concept of the Islamization of science in the integration-interconnectivity of knowledge. The concept of integration of knowledge precedes or surpasses the Islamization movement of Naquib al-Attas because this movement was motivated by the Islamic renewal movement that was born at the end of the 19th century, long before the Islamization of science was born in the 20th century.